2009
DOI: 10.1021/ef900205d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Combustion Reactivity of TGA and Drop Tube Furnace Chars from a Bituminous Coal

Abstract: Although thermogravimetric analysis (TGA) is a widely accepted technique for assessing coal combustion, conflicting trends have often been reported when relating apparent TGA reactivities to pulverized fuel (PF) burner conditions. Therefore, this paper compares the reactivity of chars generated in a drop tube furnace (DTF) to those from TGA. The implications of devolatilization temperature, heating rate and residence time are considered. For the smaller particle size ranges of the bituminous coal investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 59 publications
2
61
0
Order By: Relevance
“…N T volatiles = 100 − N T char (13) where N xchar is the mass fraction of nitrogen in the char; N T char and N T volatile are the total amount of nitrogen in the char and volatiles, respectively. Table 4 presents the calculated relative nitrogen distribution between volatiles and the residual chars at different pyrolysis temperatures.…”
Section: Nitrogen Partitioning Between Volatile and Residual Charmentioning
confidence: 99%
See 1 more Smart Citation
“…N T volatiles = 100 − N T char (13) where N xchar is the mass fraction of nitrogen in the char; N T char and N T volatile are the total amount of nitrogen in the char and volatiles, respectively. Table 4 presents the calculated relative nitrogen distribution between volatiles and the residual chars at different pyrolysis temperatures.…”
Section: Nitrogen Partitioning Between Volatile and Residual Charmentioning
confidence: 99%
“…The significance of CO 2 further highlighted by the different morphologies and significantly higher surface areas observed for biomass chars or combustion residues produced in various oxy-fuel conditions [12]. However, most of these early studies on oxy-biomass pyrolysis and combustion are carried out under TGA conditions that differ hugely from actual boiler conditions, and conflicting trends have often been reported when directly relating apparent TGA-derived combustion data to actual PF boiler conditions [13]. A drop tube furnace (DTF) is a much more suitable technique to study PF combustion reactivity key combustion parameters, particularly fast heating rates, high temperatures, short residence times and appropriate gas velocities can be replicated.…”
Section: Introductionmentioning
confidence: 99%
“…Le Manquais et al (2009) compared the intrinsic reactivity of coal char prepared at 1173, 1373 and 1573 K using a TGA which showed that the reactivity decreased with the increasing in the char-preparation temperature. The presented TGA results are similar to those obtained by Sutcu andPiskin (2009) andAsadullah et al (2010a,b), who prepared the char from loquat stones and wood at 873, 973, 1073 and 1173 K. The contradictions between the previous results and the present work may be ascribed to the differences in fuel types.…”
Section: Combustion Reactivity Tested By Tgamentioning
confidence: 99%
“…This is particularly important at high temperature and high CO 2 partial pressure. There are many possible reasons for the scatter in results in literature, which include the furnace operating temperatures used by the authors, and method of char preparation [31]. Hence, the main objectives of this study are: 1.…”
Section: Introductionmentioning
confidence: 99%